The Impact of Governance Mechanism and Managerial Overconfidence on the Value of Cash Holdings - Chang, Shen-Ho; Hsu, Feng-Yi (International Journal of Economics and Financial Issues, 2017)
This study aims to discuss the overconfident managers and the governance mechanism of the company on the value of cash held by enterprises. According to the empirical findings, the overconfident managers greatly reduces the value of the cash held by the enterprises, while the governance mechanism of the company can effectively weaken the overconfidence of the manager, and thus, significantly increase the value of the cash. An efficient governance mechanism of a company can increase the value of held cash to the level that the cash value is 2.67 times more than the cash held under an inefficient governance mechanism. Therefore, managers with overconfidence should be encouraged to hold more cash in an efficient governance mechanism. Keywords: Overconfidence, Cash holdings, Governance mechanism JET Classification: G3